TRIM6 Promotes Cell Cycle and Growth by Modulating p53 Signaling Pathway in Lung Adenocarcinoma - Lu X; Wang H; Yu T (International Journal of General Medicine)
Xi Lu,1 Haifeng Wang,1 Tingting Yu2 1Department of Thoracic and Abdominal Radiotherapy, Tumor Hospital Affiliated to Xinjiang Medical University, Urumqi, 830011, People’s Republic of China; 2Department of Thoracic Oncology, Tumor Hospital Affiliated to Xinjiang Medical University, Urumqi, 830011, People’s Republic of ChinaCorrespondence: Tingting Yu, Department of Thoracic Oncology, Tumor Hospital Affiliated to Xinjiang Medical University, No. 789 of East Suzhou Road, Urumqi, 830011, People’s Republic of China, Email 13579910597@163.comObjective: Accumulated evidence suggested that tripartite motif-containing (TRIM) proteins have a pivotal role in cancer progression. The function of TRIM6 remains largely unknown in lung adenocarcinoma (LUAD). This study aimed to clarify the role of TRIM6 in the LUAD pathogenesis.Methods: The genes involved in TRIM were selected by differential gene expression analysis and Cox regression analysis. TRIM6 was identified and verified in LUAD specimens and in paired normal tissues using immunohistochemistry. A correlation analysis was conducted comparing the expression of TRIM6 and clinicopathologic features. The role of TRIM6 in vitro and in vivo was evaluated by cell proliferation assays, cell apoptosis, cell cycle and a tumor xenograft model. Finally, we investigated downstream proteins regulated by TRIM6 by Western blotting.Results: Among TRIM proteins, TRIM6 expression was significantly elevated in LUAD tissues. The prognosis analysis demonstrated that high expression of TRIM6 was associated with unfavorable survival, which was consistent with the findings of Cox regression analysis. Further correlation analysis concluded that high TRIM6 expression was also associated with TNM staging. TRIM6 knockdown suppressed proliferation, induced cell apoptosis and cell cycle arrest in the G2/M phase. Furthermore, the exact effect of TRIM6 on LUAD cells was examined using in vivo experiments. Mechanistically, TRIM6 enhanced the biological capacity of LUAD cells through the p53 signaling pathway.Conclusion: Our study identifies TRIM6 is a potential oncogene and a prognostic target through the regulation of p53 signaling pathway in LUAD.Keywords: lung adenocarcinoma, TRIM6, cell cycle, proliferation, P53 signaling pathway